Ampullary composite gangliocytoma/neuroma and neuroendocrine tumor management - Karam, Elias; Hollenbach, Marcus; Heise, Christian; Ali, Einas Abou; Gulla, Aiste; Auriemma, Francesco; Terris, Benoît; Souche, François R.; Ponthaud, Charles de; Hank, Thomas; Caillol, Fabrice; Rhaiem, Rami; et al. (Endocrine related cancer, 2025)
Ampullary composite gangliocytoma/neuroma and neuroendocrine tumor (CoGNET), previously called ampullary gangliocytic paragangliomas, is a rare entity, with only few reported cases in the literature. This is a multicentric retrospective cohort study of patients treated with endoscopy or surgery for ampullary CoGNET. A literature review of ampullary CoGNET was also performed. Fifteen patients were included, mostly female (n = 10) with a median age of 50 years. Patients were asymptomatic in seven cases. Four patients were treated with pancreatoduodenectomy, four with transduodenal ampullectomy, and eight with endoscopic papillectomy. Clavien-Dindo III-IV complications occurred in 2 of the 8 surgical cases, but no fatal adverse events were registered. There was only one moderate endoscopic adverse event. The median length of stay was 9 days. The median tumor size was 20 mm, the R0 resection rate was 93.8%, and two patients had nodal involvement. After a median follow-up of 29 months, there was no local or distant recurrence nor death from disease. The literature review confirmed the clinical presentation and excellent outcomes of ampullary CoGNET management, especially regarding survival, even for patients with nodal or distant metastases. Overall, ampullary CoGNET are rare tumors with excellent prognosis, even with incomplete resection or nodal involvement. Treatment should be as minimally invasive as possible, and a long-term follow-up is needed.
Gesehen am 15.09.2025